Analisis Pengaruh Pengetahuan dan Kemahiran Kurikulum Ijazah Sarjana Muda Pendidikan Geografi Terhadap Pencapaian Pelajar: Analysis of the Influence of Knowledge and Curriculum Skill in Bachelor of Education (Geography) with Honors Towards Students’ Achievement - Mahat, Hanifah; Hashim, Mohmadisa; Saleh, Yazid; Che Ngah, Mohamad Suhaily Yusri; Nayan, Nasir (GEOGRAFI, 2015)
The purpose of this research is to analyze the influence of Bachelor of Education (Geography), Universiti Pendidikan Sultan Idris towards the knowledge and curriculum skill on students’ academic achievement. Analysis on effectiveness in implementation of degree education program curriculum involves inspection on the knowledge and skill of the undergraduate in their major courses while studying. This paper will describe the research finding that was done to 50 students of final year from Bachelor of Education (Geography) 2015 by questionnaire. The questionnaire variables include the three major variables which are knowledge, skills and student academic achievement. Knowledge variable was divided into six sub variable (major courses knowledge, curriculum, co-curriculum, career goal, teaching & learning and teaching & learning evaluation) while skill variable consist sub variable (technology education skill, communication skill and soft skill) and final variable is student’s academic achievement. Item for each variable is developed and customized based on Ministry of Education Malaysia graduate tracer study and expert validity. Pekali Spearman analysis was chosen in analyzing the relationship on students’ achievement. Finding on Spearman correlation test showed that there are significant positive relations between major subject skills on undergraduates’ class honors achievement. Besides, it was found that the relationship between major subject skill with co-curriculum knowledge is stronger compared to other variables. Regression logistic analysis also clarified that there are only two variables that have the significant influence against undergraduate’s class honours achievement which are co-curriculum knowledge and subject skill. This means student that has relatively high skill in major subject and co-curriculum knowledge has the capability to achieve better class honours degree. Overall, this study is important to review variables that influence students’ achievement in assisting the faculty and department to improve students’ achievement in the future.